TENCON 2009 - 2009 IEEE Region 10 Conference 2009
DOI: 10.1109/tencon.2009.5396110
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical effect on determining threshold voltage of trigate FinFET using self-consistent analysis

Abstract: The quantum definition based threshold voltage has been evaluated for triple-gate (TG) SOI FinFETs using selfconsistent Schrödinger-Poisson solver. Although a new quantum definition of threshold voltage for multiple gate SOI MOSFETs has been provided in recent literature, in-depth analysis of quantization effects on threshold voltage calculation for highly scaled TG FinFETs is yet to be done. In this paper, the electrostatics of the device has been explored from a quantum mechanical point of view for variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Therefore, high-k gate dielectrics are the most promising alternatives which decrease leakage current at the cost of enhanced gate capacitance. Hafnium oxide is employed as a promising gate oxide material because of its excellent interface with Si, high-k value (22), big bandgap (5.6 eV), and conduction band offset (1.4 eV) with regard to Si. Most significantly, a decent electrical interaction with Si makes it a prospective alternative to silicon dioxide [17][18][19][20][21].…”
Section: Structural Dimensions Ie W mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, high-k gate dielectrics are the most promising alternatives which decrease leakage current at the cost of enhanced gate capacitance. Hafnium oxide is employed as a promising gate oxide material because of its excellent interface with Si, high-k value (22), big bandgap (5.6 eV), and conduction band offset (1.4 eV) with regard to Si. Most significantly, a decent electrical interaction with Si makes it a prospective alternative to silicon dioxide [17][18][19][20][21].…”
Section: Structural Dimensions Ie W mentioning
confidence: 99%
“…A self-consistent Schrodinger-Poisson solver was reported by Emran Md. Amin et al But without using a complex Schrodinger-Poisson equation, this paper makes an effort to indicate the effect of width quantization on the threshold voltage [22]. Saha et al reported a triple materials gate (TMG) TG-FinFET [23].…”
Section: Structural Dimensions Ie W mentioning
confidence: 99%
“…To address these challenges, FinFETs stand out as prospective electronic devices [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] due to their improved scalability and ability to control SCEs. The functionality of nanoscale FinFETs is now transitioning into a region where quantum mechanical effects such as quantum confinement effects are becoming discernible [31][32]. This confinement alters the energy band structure of the material, leading to discrete energy levels and affecting electron mobility.…”
Section: Introductionmentioning
confidence: 99%
“…This device uses low power to change from a turn off to turn on, same to electrical switch. It uses the bias voltage about 0.2 -0.3 volts to change working state [2]. In operating of FinFET, it giving many variables and the one significant is carrier mobility [3].…”
Section: Introductionmentioning
confidence: 99%